THE EFFECT OF DEXAMETHASONE ON CALCIUM HOMEOSTASIS AND THE EXPRESSION OF TGF-B1 OF WISTAR RAT’S FEMUR BONE POST TRANSPLANTATION WITH DEMINERALIZED FREEZE-DRIED BOVINE BONE XENOGRAFT - Sudimantini, Luh Made; Adji, Dhirgo; Wuryastuty, Hastari (Buletin Veteriner Udayana, 2020)
This research aims to evaluate the safety of dexamethasone use as an anti-inflammatory and analgesic on the handling of femur fracture of rats by bone graft method. The sample used was 32 male Wistar rats aged 2 months were divided into two groups, 16 rats for each. Group I was fractured rats and fixed with intramedullary pin without bone graft, whereas Group II was fractured and fixed with intramedullary pin and demineralized freeze-dried bovine bone xenograft (DFDBBX). Group I and II were then divided into two groups for each, Group IA, IB, IIA, and IIB, eight rats for each. Group IA and IIA were not injected with dexamethasone, whereas Group IB and IIB were injected with dexamethasone 0.5 mg/kg BW/ day intramuscularly. At the end of the first week, blood was collected from eight rats (two rats for each) of Group IA, IIA, IB, and IIB for total leucocytes and blood Calcium analysis. Urine was also collected for urine Calcium analysis. Rats were then killed to collect the femur for histopathologic analysis using HE staining and immunohistochemistry to analyze the expression of TGF?-1 using Streptavidin-biotin method. Subsequent sampling was conducted at the end of 2nd, 4th, and 8th weeks of treatment, respectively. The total data of leucocytes, blood, and urine Calcium were statistically analyzed using a 2x2x4 factorial method, while the histopathologic and immunohistochemistry specimens were analyzed descriptively under the microscope based on the alteration of the bones. The statistical analysis showed that dexamethasone increased the concentration of urine Calcium (p<0,05), the concentration of blood Calcium insignificantly (p>0,05) affected by dexamethasone but cause homeostatic calcium disorder and the total leucocytes significantly (p<0,05) affected by grafted materials. Histopathologic analysis of the femur showed that there was an increased infiltration of inflammatory cells in the fracture area from the group untreated with dexamethasone. Whereas the immunohistochemistry analysis showed positive results from all groups. Based on the whole analysis, it can be concluded that although dexamethasone depressed inflammation process, it can also disturb the fracture healing process.